2022
DOI: 10.3389/fenvs.2022.972354
|View full text |Cite
|
Sign up to set email alerts
|

The role of environmental taxes and stringent environmental policies in attaining the environmental quality: Evidence from OECD and non-OECD countries

Abstract: Numerous economies focus on attaining a clean environment by applying environmental policies and green technology. This study examined the impact of GDP growth, non-renewable, technological change, environmental tax, and strict regulations on an ecological footprint for the Organization for Economic Cooperation and Development (OECD) and Non-OECD (not members of OECD) economies from 1990 to 2015. This analysis applied the Cross-Sectionally Augmented Auto-Regressive Distributed Lag (CS-ARDL) to identify the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Studies have shown that higher taxes on carbon emissions lead to a decrease in the use of fossil fuels and a reduction in CO 2 emissions, which can contribute to addressing climate change [83]. Imposing taxes on activities that contribute to the ecological footprint, such as resource exploitation and pollution, could encourage the adoption of sustainable practices and drive investments in renewable energy, energy efficiency, and waste reduction technology [84]. Moreover, revenue generated from environmental taxes can support initiatives for environmental conservation, biodiversity preservation, and sustainable development, ultimately reducing the ecological footprint (OECD, 2019).…”
Section: Variables Definition and Anticipated Sign Of Coefficientsmentioning
confidence: 99%
“…Studies have shown that higher taxes on carbon emissions lead to a decrease in the use of fossil fuels and a reduction in CO 2 emissions, which can contribute to addressing climate change [83]. Imposing taxes on activities that contribute to the ecological footprint, such as resource exploitation and pollution, could encourage the adoption of sustainable practices and drive investments in renewable energy, energy efficiency, and waste reduction technology [84]. Moreover, revenue generated from environmental taxes can support initiatives for environmental conservation, biodiversity preservation, and sustainable development, ultimately reducing the ecological footprint (OECD, 2019).…”
Section: Variables Definition and Anticipated Sign Of Coefficientsmentioning
confidence: 99%
“…The model was found to have benefited financially from environmental tax money. 1 unit change in gross domestic product (GDP) will increase environmental quality by 0.52 units 98 . In other words, the amount of money collected from environmental taxes is a key indicator of economic growth due to the fact that these taxes have a positive correlation with the growth of the economy 99 .…”
Section: Hydrothermal and Thermochemical Technologiesmentioning
confidence: 99%
“…1 unit change in gross domestic product (GDP) will increase environmental quality by 0.52 units. 98 In other words, the amount of money collected from environmental taxes is a key indicator of economic growth due to the fact that these taxes have a positive correlation with the growth of the economy. 99 In the EU, municipal garbage recycling rates were found to be high, and this had a positive impact on GDP per capita.…”
Section: Advancements In Biowaste Refining and Circular Economy's Sig...mentioning
confidence: 99%
“…Among these gases, carbon dioxide emissions are identified as the predominant factor contributing to anthropogenic GHG emissions. Previous studies have frequently employed CO 2 emissions as a key indicator to assess the extent of environmental catastrophes (Abid et al 2022 ; Chen et al 2022 ). We have used CO 2 as a representative of climate change, and the data for OECD countries is extracted from WDI ( 2021 ).…”
Section: Econometric Modelingmentioning
confidence: 99%
“…The pathway to effectively address environmental crises relies heavily on the policy objectives set forth by various governments and international authorities and their strategic policy decisions, which play a crucial role in shaping environmental outcomes (Dechezleprêtre et al 2011 ; Wenbo and Yan 2018 ). By adhering to these strategies, nations can effectively curb harmful emissions and enhance energy efficiency, fostering sustainable development and resilience in the face of global environmental challenges (Chen et al 2022 ). Hille et al ( 2020 ) posited that to maximize the advantages derived from environmental policies; it is imperative to implement an approach over a prolonged duration, thereby demonstrating a commendable level of regulatory consistency in the realm of environmental governance.…”
Section: Introductionmentioning
confidence: 99%